Water management and sustainable development in Pakistan: environmental and health impacts of water quality on achieving the UNSDGs by 2030 - Ishaque, Waseem; Sultan, Khalid; ur Rehman, Zia (Frontiers in Water, 2024)
Water security is an evolving national security challenge for Pakistan. Combined with water scarcity, the quality of drinking water is fast depleting, and the available drinking water is contaminated due to many reasons, however, the ecological chain's impact is pronounced. Despite the strong realization by the government for the provision of clean drinking water to the inhabitants, and the use of smart technology for irrigation as it consumes 60%-70% of water to conserve available water resources, the policy implementation is a daunting challenge. The study argues that surface and subsurface drinking water in Pakistan is being contaminated very quickly, creating several health risks and potential human security issues. The study examines the quality of drinking water through laboratory tests by collecting samples from selected urban and rural areas as a case study and examining these against minimum safe ranges given in the international and national clean drinking water parameters. As a result of laboratory testing, it has been revealed that the quality of drinking water in Pakistan is depleting sharply and the evolving situation, if not addressed in time, has the potentials of becoming the biggest health risks in coming years. As the water quality is consistently deteriorating and water availability is gradually receding, the attainment of United Nations Sustainable Development Goals (UNSDGs) on water by 2030 is becoming a distant possibility. As a timely input to relevant institutions and government ministries, the study comprehensively highlights the challenges of water scarcity and water quality in Pakistan and proffers recommendations for addressing the multidimensional water security issues on sustainable basis and achieving UNSDGs number 6 on access to clean water and sanitation for all by 2030.